The relationship between trait anxiety and sleep quality in college students: an exploratory analysis of physical activity as a moderator - Zhong, Liyang; Ma, Xiaochen; Li, Sen; Yu, Ling (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to examine the association between trait anxiety and sleep quality among college students and to assess whether different levels and components of physical activity (PA) moderate this relationship.MethodsA cross-sectional survey was conducted among 2,902 college students. Standardized instruments were used to evaluate trait anxiety, sleep quality, and PA levels. Moderation regression models were constructed to test interaction effects.ResultsTrait anxiety was significantly associated with decreased overall sleep quality and impairments across all sleep subdimensions. PA level significantly moderated the relationships between trait anxiety and four dimensions of sleep: sleep quality, sleep latency, sleep efficiency, and daytime dysfunction. Stronger buffering effects were observed under conditions of high intensity, long duration, and high frequency of PA.ConclusionHigh-intensity, long-duration, and high-frequency physical activity may help alleviate anxiety-related sleep disturbances in college students, exhibiting a clear dose–response effect. The findings support exercise as a non-pharmacological strategy for improving mental health.